Angiotensin receptors (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database - Alexander, Wayne; Bernstein, Kenneth E.; Catt, Kevin J.; de Gasparo, Marc; Dhanachandra Singh, Khuraijam; Eguchi, Satoru; Escher, Emanuel; Goodfriend, Theodore L.; Horiuchi, Mastgugu; Hunyady, László; et al. (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
The actions of angiotensin II (Ang II) are mediated by AT1 and AT2 receptors (nomenclature as agreed by the NC-IUPHAR Subcommittee on Angiotensin receptors [61, 152]), which have around 30% sequence similarity. The decapeptide angiotensin I, the octapeptide angiotensin II and the heptapeptide angiotensin III are endogenous ligands. losartan, candesartan, telmisartan, etc. are clinically used AT1 receptor blockers.